Strategi Guru dalam Menggunakan Canva sebagai Media Interaktif dalam Pembelajaran Nilai Keislaman di TK Islam Al-Furqon Desa Pedamaran 1 Kecamatan Pedamaran Kabupaten Ogan Komering Ilir - Widianti Widianti; Ahmad Sopian; Muhammad Roihan Alhaddad (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to describe teachers' strategies in using Canva as an interactive medium in Islamic values ​​learning. This learning is carried out once a week and is adjusted to the needs and developments of the times to improve the quality of Islamic values ​​learning. The material presented includes the basics of Islamic teachings, such as understanding prayer and its movements, hijaiyah letters, daily prayers, and the use of good words in Islam. The research method used is descriptive qualitative research. Data sources in this study consist of primary data and secondary data, with data collection techniques through observation, interviews with the principal, class teachers, and students, as well as documentation of learning activities. Data analysis techniques used are data reduction, data presentation, and conclusions or verification. The results of the study show that: 1) Teachers' strategies in using Canva as an interactive medium in Islamic values ​​learning are carried out through the use of colorful images and interesting animations, Islamic animation videos, and interactive question and answer activities. 2) The use of Canva can increase children's interest, attention, and activeness in participating in learning. 3) Canva is effective as a learning medium for Islamic values ​​because it helps children more easily understand the material presented. These findings indicate that using Canva as an interactive medium is effective in supporting the learning of Islamic values ​​in early childhood at Al-Furqon Islamic Kindergarten and increasing children's engagement during the learning process.